Mengembangkan Aspek Sosial Anak Usia Dini Dengan Metode Permainan - Ana Isnainiyah; Maulidatul Afifatur; Ramadha Tsulatsi Hajar (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This study presents the improvement of early childhood development through the game method. This aims to determine the application of the game method in early childhood and what efforts are used to improve the social development of early childhood. Games  are  physical  activities  in  the  form  of  small  groups  that  allow  collaboration between students. There are various kind of games that are applied to early childhood effectively so that they can optimize the social development of early childhood both at school and the surrounding and environtment. Analysis of the data used by observation, interviews and documentation. Sources of data from this study include the community, teachers,  and  children.  Based  on  the  results  of  the  study,  it  can  be  interpreted  that applying the game method to early childhood in social development by getting used to grouping children randomly can increase cooperation between students so that children’s ability to socialize with friends, teachers and surrounding environment also increases.